2022
DOI: 10.4102/safp.v64i1.5533
|View full text |Cite
|
Sign up to set email alerts
|

Telehealth in South Africa: A guide for healthcare practitioners in primary care

Abstract: The use of telehealth is becoming a prevalent feature in clinical practice worldwide, partly because of advances in medical and telecommunications technology. The coronavirus disease 2019 (COVID-19) pandemic has been a key driver in justifying the accelerated use of telehealth, leading to healthcare practitioners (HCPs) utilising virtual consultations more avidly. Although challenges remain, recent data have shown that remote consultations are feasible, safe and effective in South Africa (SA) and that HCPs sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…22 (52.5%) articles described the importance of, or methods for, assessing before virtual appointments to evaluate whether virtual care is a viable, useful method of care delivery for a patient’s particular needs 22–43. For example, one article described the importance of establishing a ’relationship’ between healthcare providers and patients to assess virtual care appropriateness23; another three articles noted that patients generally have a positive view of psychological screening assessments conducted prior to a virtual visit 24–27…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…22 (52.5%) articles described the importance of, or methods for, assessing before virtual appointments to evaluate whether virtual care is a viable, useful method of care delivery for a patient’s particular needs 22–43. For example, one article described the importance of establishing a ’relationship’ between healthcare providers and patients to assess virtual care appropriateness23; another three articles noted that patients generally have a positive view of psychological screening assessments conducted prior to a virtual visit 24–27…”
Section: Resultsmentioning
confidence: 99%
“…Ten articles (22.5%) focused on providing training for virtual care. Seven articles (17.5%) recommended that staff receive proper training and adopt an understanding and individualised communication approach 22 23 27 41–43 52. Two articles (5%) reported that providers should strengthen their communication skills by enrolling in training courses or programmes 57 60.…”
Section: Resultsmentioning
confidence: 99%
“…These are understood to be providing opportunities for greater access to consultations and counseling. COVID has been described as a "key driver" in adopting telehealth at a community level and increasing efficiency in delivering clinical services to patients with chronic illnesses [26] . In this context, discussions about and decisions around assisted reproduction treatment were only one of many forms of care that changed mode.…”
Section: Discussionmentioning
confidence: 99%
“…There is growing support for telepractice internationally (Camden & Silva, 2021, Cleffi et al, 2022Gefen et al, 2022;Hall & Luechtefeld, 2021) and nationally (Rabe, 2022;Adebayo et al, 2021). In our annual review of services, therapists in the STA department indicated that telepractice allowed for increased caregiver engagement and generalization of activities in the home environment, thereby allowing for improved family centered care (Camden & Silva, 2021, Cleffi et al, 2022Gefen et al, 2022;Hall & Luechtefeld, 2021).…”
Section: Clinical Implementationmentioning
confidence: 99%